Communicating User Experience: Applying Local Strategies Research to Digital Media Design - Milburn, Trudy (2015)
Communicating User Experience illustrates how the use of Local Strategies Research (LSR) methodologies enables designers to understand the cultural implications for user actions and practices in a...
Keywords: dept.aa

Translating Tasks for International Classrooms - Townsend, Rebecca M; Milburn, Trudy (Internationalizing the Communication Curriculum in an Age of Globalization, 2019)
This chapter presents a case study from an American university’s partnership with a Polish university. The case involves an assignment to international students studying for their master’s degrees: translating “key concepts in intercultural dialogue” for publication on the Center for Intercultural Dialogue’s website. There were several problems of translation of the task assignment. One problem is the translation of expectations. Learning outcomes occur for professors, too, and the chapter offers reflection on what lessons were realized for future teaching in the international classroom.
Keywords: dept.aa